Synaptic and complement markers in extracellular vesicles in multiple sclerosis - Bhargava, Pavan; Nogueras-Ortiz, Carlos; Kim, Sol; Delgado-Peraza, Francheska; Calabresi, Peter A; Kapogiannis, Dimitrios (Multiple sclerosis, 2021)
Synaptic loss is a feature of multiple sclerosis pathology that can be seen even in normal-appearing gray matter. Opsonization of synapses with complement components may underlie pathologic synapse loss. We sought to determine whether circulating neuronal-enriched and astrocytic-enriched extracellular vesicles (NEVs and AEVs) provide biomarkers reflecting complement-mediated synaptic loss in multiple sclerosis. From plasma of 61 people with multiple sclerosis (46 relapsing-remitting multiple sclerosis (RRMS) and 15 progressive MS) and 31 healthy controls, we immunocaptured L1CAM + NEVs and GLAST + AEVs. We measured pre- and post-synaptic proteins synaptopodin and synaptophysin in NEVs and complement components (C1q, C3, C3b/iC3b, C4, C5, C5a, C9, Factor B, and Factor H) in AEVs, total circulating EVs, and neat plasma. We found lower levels of NEV synaptopodin and synaptophysin in MS compared to controls ( < 0.0001 for both). In AEVs, we found higher levels of multiple complement cascade components in people with MS compared to controls; these differences were not noted in total EVs or neat plasma. Strikingly, there were strong inverse correlations between NEV synaptic proteins and multiple AEV complement components in MS, but not in controls. Circulating EVs could identify synaptic loss in MS and suggest a link between astrocytic complement production and synaptic loss.